Functional analysis of allene oxide cyclase, MpAOC, in the liverwort Marchantia polymorpha. (August 2015) - Yamamoto, Yusuke; Ohshika, Jun; Takahashi, Tomohiro; Ishizaki, Kimitsune; Kohchi, Takayuki; Matusuura, Hideyuki; Takahashi, Kosaku
Graphical abstract: AOC in the octadecanoid pathway is functional and OPDA acts as a signaling molecule regulating growth and response to wounding in the model liverwort Marchantia polymorpha . Highlights: OPDA is present in the model liverwort Marchantia polymorpha. OPDA demonstrates growth inhibitory activity in M. polymorpha. An allene oxide cyclase (AOC) in M. polymorpha shows AOC activity. Feedback regulation of the octadecanoid pathway is conserved in M. polymorpha . Overexpression of MpAOC suppressed M. polymorpha growth. Abstract: 12-Oxo-phytodienoic acid (OPDA) is an intermediate in jasmonic acid (JA) biosynthesis. OPDA exerts JA-dependent and JA-independent biological effects; therefore, it is considered a signaling molecule in flowering plants. OPDA is induced by bacterial infection and wounding and inhibits growth in the moss Physcomitrella patens . The functions of OPDA and allene oxide cyclase (AOC) in the liverwort Marchantia polymorpha were explored, which represents the most basal lineage of extant land plants. The analysis of OPDA showed that it is present in M. polymorpha and is increased by wounding. OPDA has been suggested to be involved in the response to environmental stresses. Moreover, OPDA showed growth inhibitory activity in M. polymorpha . Nonetheless JA in M. polymorpha was not found in this study. AOC synthesizes OPDA from an unstable allene oxide. A database search of the M. polymorpha genome identified only a putative gene encoding allene oxide cyclase (MpAOC). Recombinant MpAOC showed AOC activity similar to that in flowering plants. MpAOC was localized to chloroplasts, as in flowering plants. Expression of MpAOC was induced by wounding and OPDA treatment, and positive feedback regulation of OPDA was demonstrated in M. polymorpha . Overexpression of MpAOC increased the endogenous OPDA level and suppressed growth in M. polymorpha . These results indicate the role of OPDA as a signaling molecule regulating growth and the response to wounding in the liverwort M. polymorpha.